Mathematical Resilience and Bis-VOLKS Misconceptions in School Mathematics Learning - Bistari, Bistari (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
When mastering mathematical concepts, it is rather difficult to avoid misconceptions. Beginner's understanding that does not match scientific concepts is often found in learners and even teachers. The effect of a learner's misconception is certainly different from the teachers. An educator's misconception can be misleading for himself and around his friends only. However as a teacher, misconceptions can affect many learners. Especially those who do not have stability and resilience in concept mastery. The reliance or resilience that learners have is not only emotional and attitudinal, but cognitive resilience or mastery that is measurable and ready with scientific reasons should reach many learners. There are many theories of misconception from experts. The author introduces the Bis-VOLKS misconceptions, namely: (1) visual misconceptions; (2) operational misconceptions; (3) literational misconceptions; (4) correlational misconceptions; and (5) spatial misconceptions. Visual can be defined as anything that the eye can see.  Visual misconception means an error in perceiving something through eye observation. There are four visual elements that need to be known. Operational misconceptions are errors that arise as a result of incorrect basic and advanced operations. Literacy can be defined as the ability to read, write, and understand written texts. Literacy includes the ability to process, analyze and present information through text. About literational, the concept is broader and includes more than just the ability to read and write. Correlational can be interpreted as a study that explores the causal relationship of two or more aspects. Correlational misconceptions result from errors that arise in uncovering different causes and effects in scientific concepts. Spatial misconceptions. Spatial ability is an ability that includes spatiality and all its applications.  Spatial ability refers to a person's ability to understand and manipulate objects in space. It involves the perception and understanding of spatial relationships between objects, directions, and surrounding space.